Pengaruh Eradikasi Gulma terhadap Perkembangan Populasi Wereng Hijau dan Kejadian Penyakit Tungro pada Padi - Raden Heru Praptana; Wasis Senoaji (Jurnal Ilmu Pertanian Indonesia, 2017)
Tungro is one of the important diseases in rice that is still a constraint to increased productivity. Tungro disease caused by a tungro viruses that is transmitted by green leafhoppers in a semi persistent manner. The presence of weeds can cause yield losses of rice and is a potential host plant of tungro viruses. Eradication of weeds is an attempt to eliminate the source of inoculum of tungro viruses. The research objective was to determine the effect of weed eradication on the development of green leafhopper population and the incidence of tungro disease. The study was conducted in an experimental field of Tungro Disease Research Station, Lanrang Village, Sidenreng Rappang District, South Sulawesi at rainy season and dry season 2014. The experiment was arranged in a randomized complete block design with 8 eradication treatments and 4 replications. The parameters include the observation of weed species that grow in each plot and embankment planting, green leafhopper population density and the number of infected plants by tungro viruses. Observations in the planting is done at 2, 4, 6, and 8 weeks after planting (WAP). The observations of weeds and green leafhopper population was also conducted on the field before eradication. The results showed that the weeds potential as a source of inoculum were Cyperus rotundus, C. iria, Fimbristylis miliacea, and E. colonum. Eradication of weeds before and after planting through both mechanical and herbicide applications tended to suppress the green leafhopper populations and tungro disease incidence.